The perception of the police by the poor: a case study of four communities in Oyo State - Nigeria (1997)
The Nigerian Police force is the primary law enforcement agency in Nigeria. It is the first contact that a person has with the criminal justice system. The members of the police force perform so many functions and they deal closely with the people. There is a legal adage which says that “The law is no respecter of persons". Therefore, during the interaction of the police with the members of the public, all persons are expected to | be treated equally without regards to sex, age, ethnic group, educational qualification or wealth. Furthermore, to enhance the relationship between members of the public and the police, the police coined an expression that “police is your friend”. The police come into frequent contact with certain classes of people than others in the performance of certain duties. The poor fall into this class as they come into friction with the police often. For mutual understanding between the police and the public, it is pertinent to examine the truth of this police saying from the perspective of the poor. Oyo State is one of the thirty-six States in Nigeria. Being a large Slate, this study is limited to a few communities in Oyo State, where the poor are situated. The poor are defined for the purposes of this paper and are divided into the rural and urban Areas. This paper highlights the perception of the police by the poor. The poor perceives the police as partial, corrupt, time wasters, unorganised, and inefficient. The problems of the Police Force are examined. The police stated some of these problems to include manpower problems, logistic problems, poor image of Ike police by the society, lack of funds and poor salary. This paper suggest that them is need for immediate and constant recruitment into the police force to beef up manpower, a review of the present salary structure and sufficient motivation for members of the Police force, provision of modem equipment and adequate office accommodation and materials.